Early detection of children development: A pilot study - Wijayanti, Maulintan; Astuti, Retna Tri; Pinilih, Sambodo Sriadi (Innovation in Health for Society, 2022)
School-age children's development stages are a significant time for the continuity of children's development because school age is a period where children gain knowledge and experience that can bring them into adolescence. The role of parents as people closest to children also affects the process of child development, one of which is providing stimulation to children to achieve optimal growth and development. This study aims to describe the early detection and stimulation of development in school-age children. The method used in this research is a case study using purposive sampling. The sample used was a 9-year-old school-age child who experienced a lack of developmental stimulation in children. The research data was taken using participatory observation methods, unstructured interviews and documentation. The results showed that providing health education can increase developmental motivation in children. Health education is useful for increasing developmental stimulation in children to achieve optimal growth and development. Keywords: Children development; nursing care; nursing assessment; child growth stimulation; child health